On the Convergence of Asynchronous Nested Matrix Multisplitting Methods for Linear Systems (Journal of Computational Mathematics, 2021)
A class of asynchronous nested matrix multisplitting methods for solving large-scale systems of linear equations are proposed, and their convergence characterizations are studied in detail when the coefficient matrices of the linear systems are monotone matrices and $H$-matrices, respectively.
Keywords: Solution of linear systems; Asynchronous parallel iteration; Matrix multisplitting; Relaxation method; Convergence.